The ceremony of Halad Chadavne - Mumbai Archive Project Team (Jio Institute, 2024)
Halad chadavane, also known as the haldi (turmeric) ceremony, is held at the homes of both the bride and the groom. The bride and the groom wear white attire that becomes dyed yellow during the ceremony. Typically, this event takes place either on the morning of the wedding day or the day before.